Pengaruh Lingkungan Keluarga Terhadap Kepribadian Anak Di Desa Waringinsari Barat Tahun 2020 - Ningsih, Yeni Yulia; Palupi, Rini; Kusuma, Anggi (Universitas Aisyah Pringsewu (UAP) Lampung, 2021)
The family is the first ward to shape the character and attitude of a child. According to Slameto (2010). The family environment is the first and foremost influence of one's life, growth, and development. The family environment is the oldest educator, informal, first and foremost experienced by children and educational institutions that parents are responsible for maintaining, caring, protecting and educating children to grow and develop well (Hasbullah, 2009). The term personality or in English Personality comes from Ancient Greek, prosopon or persona meaning